Engkapsulasi Ekstrak Buah Mengkudu (Morinda Citrifolia L.) Menggunakan Ekstrak Kulit Jeruk (Citrus X limon L.) - juliani, evi; siregar, Syakir naim (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2023)
Indonesia is famous for being a source of basic ingredients for herbal medicines. Noni is one of the most widely used plants for traditional medicine. Noni contains many compounds that are beneficial to health, so it is necessary to process the noni to be used as a practical herbal medicine and does not have an unpleasant odor to the public or the distinctive odor of the noni fruit. The study was conducted using a factorial Completely Randomized Design (CRD) consisting of two factors, namely: Factor I: Comparison of Noni Extract (Morinda citrifolia L) and Lemon Peel Extract (Citrus x limon) (E) consisting of 4 levels, namely: E1 = 150:135, E2=155:130, E3=160 : 125, E4=165:120. Factor II: Drying Time (P) consists of 4 levels, namely: P1 = 3 hours, P2 = 4 hours, P3 = 5 hours, P4 = 6 hours. Comparison of 155:130 material with 4 hours of drying time gives a moisture content of 3.71%, yield of 8.175 %.